Korelasi Profitabilitas, Ukuran Perusahaan, dan Penjualan Bersih pada Struktur Modal Kepemilikan Properti dan Real Estate di Bursa Efek Indonesia 2017 - Syahrudi Syahrudi; Abdul Azim Wahbi; Prasetio Ariwibowo (LITERATUS, 2021)
Each the property and real estate industries are one of the industries listed in the Indonesian stock exchange. Property and real estate characteristics are those whose assets are rated to have high investment value, and are fairly safe and stable. Property and realestate development will naturally attract investors as land and building prices rise, land offers are steady while demand will continue to increase as the population increases and the growing human need for housing, offices, and shopping centers word/phrase is separated by commas The purpose of research to analyze the impact of profitability (roa) on capital structures (der), corporate size (pp), and sales growth (pp) on property and real estate firms in the Indonesian stock exchange in 2017-2019. As for the method used in this study using a more impressive sampling method using specific criteria in the sampling taken. And the sample used in this study is 32 real estate and property companies. Analysis has shown that there is influence for profitability (roa) on capital structures (der), corporate size, and sales growth (pp) (x) on property and real estate companies (y).